Outcomes of Patients who Received Bailout Thrombectomy for Primary Percutaneous Coronary Intervention - Osama, Badr Mansoor, Syed Mohammad Ali Zain Shah, Massiha Gulzar Ahmad, Ahmad Mustafa, Faraz Ali, Muhammad Ali Khan, Gulzar Ahmad, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The purpose of this study was to compare outcomes among patients undergoing primary percutaneous coronary intervention with and without bailout thrombectomy. Study Design: Observational/ cross sectional study. Place and Duration: This observational/cross sectional study was conducted at Interventional Cardiology, National Institute of Cardiovascular Diseases, Karachi, Pakistan in the period from March,2022 to August, 2022. Methods: Total 140 patients of both gender had ST elevation myocardial infarction were presented for primary percutaneous coronary intervention. Patients were included after getting informed written consent for detailed demographics such as gender, age, comorbidities and history of CAD. We divided patients into two groups. Group I received only PPCI in 70 cases and 70 cases of group II received only PPCI with bailout thrombectomy. After PPCI comma results of both groups were compared. To analyzation of data, we use SPSS 18.0. Results: Among all presented cases, 80 (57.1%) were male patients and 60 (42.9%) were females. The patients mean age in group I was 53.17±11.62 years and in group II mean age was 55.9±10.94 years. Diabetes mellitus was the most common comorbidity found among both groups 35(50%) in group I and 27(38.6%) in group II followed by hypertension 21(30%) in group I and 24(34.3%) in group II. Family history of coronary artery disease (CAD) in group I was 19(27.1%) and in group II was 23(32.9%).There was no significance difference found in both groups in terms of mortality. There was significant higher number of renal impairment, stroke, heart failure, excess bleeding and renal infarction in group II as compared to group I with p value<0.05. Hospital stay was also higher in group II as compared to group I with p value<0.04. Conclusion: It is determined that patients who underwent bailout thrombectomy for percutaneous coronary intervention (PCI) had a significant risk of comorbidities. Between the two groups, there was no discernible variation in mortality. Those who underwent bailout thrombectomy, however, had higher rates of post-procedure stroke and renal impairment. Keywords, Bailout thrombectomy, Outcomes, ST-segment elevated myocardial infarction, PPCI.